THE ROLE OF FRESH AZOLLA LOCAL BESUKI’S IN IMPROVING THE NITROGEN USE EFFICIENCY OF PADDY FIELD - HASBI, HUDAINI (Innovare Journal of Agricultural Sciences, 2019)
The development of management techniques to improve the poor N use efficiency by lowland rice (Oryza sativa L.) and reduce the high N losses has been an important focus of agronomic research. The potential of an Azolla cover in combinationwith urea was assessed under field conditions in Jember, East Java,Indonesia. Two on-station field experiments were established in the 1998–1999 dry season and eight on-farm experiments per season were carried out in the 2000–2001 wet and dry seasons. Treatment combinations consisting of N levels applied alone or combined with Azolla were evaluated with respect to floodwater chemistry, 15N recovery, crop growth, and grain yield. A full fresh Azolla cover on the floodwater surface at the time of urea application prevented the rapid and large increase in floodwater pH and floodwater temperature. As a consequence, the partial pressure of ammonia (ρNH3), which is an indicator of potential NH3 volatilization, was significantly depressed. 15N recovery was higher in plots covered with Azolla where the total 15N recovery ranged between 77 and 99%, and the aboveground (grain and straw) recovery by rice ranged between 32 and 61%. The tiller count in Azolla-covered plots was significantly increased by 50% more than the uncovered plots at all urea levels. Consequently, the grain yield was likewise improved. Grain yields from the 16 on-farm trials increased by as much as 40% at lower N rates (40 and 50 kg N ha−1) and by as much as 29% at higher N rates (80 and 100 kg N ha−1). In addition, response of rice to treatments with lower N rates with an Azolla cover was comparable to that obtained with the higher N rates without a cover. Thus, using Azolla as a surface cover in combination with urea can be an alternative management practice worth considering as a means to reduce NH3 volatilization losses and improve N use efficiency.